2007
DOI: 10.1002/hyp.6698
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between drought and solar irradiation variables

Abstract: Abstract:Drought prediction for in many regions of the world has critical importance for strategic planning agriculture and water management. The occurrence of droughts cannot be predicted with certainty and thus must be treated as random variables. It is the main purpose of this paper to develop a new concept of drought features assessments based on triple drought related hydrometeorological and meteorological variables, namely, rainfall, solar irradiation and sunshine duration. Equal standard rainfall lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Z-Score is frequently computed in drought studies (Akhtari et al, 2009;Komuscu, 1999;Morid et al, 2006;Patel et al, 2007;Tsakiris and Vangelis, 2004;Wu et al, 2001). To differentiate it from SPI, Z-Score is sometimes called the standardized monthly precipitation (SMP) (Sirdas and Sahin, 2008). Since the original SPI (Mckee et al, 1993) has been commonly used to fit a gamma distribution, calling as Z-Score or SMP instead of SPI for further studies is better when the distribution type is normal.…”
Section: Statistical Z Scorementioning
confidence: 99%
“…Z-Score is frequently computed in drought studies (Akhtari et al, 2009;Komuscu, 1999;Morid et al, 2006;Patel et al, 2007;Tsakiris and Vangelis, 2004;Wu et al, 2001). To differentiate it from SPI, Z-Score is sometimes called the standardized monthly precipitation (SMP) (Sirdas and Sahin, 2008). Since the original SPI (Mckee et al, 1993) has been commonly used to fit a gamma distribution, calling as Z-Score or SMP instead of SPI for further studies is better when the distribution type is normal.…”
Section: Statistical Z Scorementioning
confidence: 99%
“…The Z ‐score for SPI trend significantly decreased in regions with low elevation and high solar radiation in the short‐, seasonal‐, and medium‐term drought durations for the spring months of April and May. Sirdas and Sahin () have shown that solar radiation and sunshine duration both increases drastically during the dry seasons, whereas solar radiation is the lowest during the wet seasons. In addition, the study demonstrated that the sunshine duration during the dry seasons has a significant effect on droughts.…”
Section: Discussionmentioning
confidence: 98%
“…As well as the Deciles Precipitation Index, the Effective Drought Index (EDI), and the SPI, their values are standardized; which allows detailed comparison between regions with different climates (Byun andWilhite 1999, Danandeh et al 2019). Because the prediction of drought periods is of high importance for water planning around the world, forecasting models must become more robust and simple (Sirdas and Sahin 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Any proposed index would include loss of soil moisture, change in groundwater storage or decrease in reservoir levels (Zargar et al 2011, Van Loon andLaaha 2015) as the main inputs. Because the occurrence of droughts cannot be predicted with certainty, it should be studied as a random variable (Sirdas and Sahin 2008).…”
Section: Introductionmentioning
confidence: 99%